2020
DOI: 10.1038/s41598-020-57979-8
|View full text |Cite
|
Sign up to set email alerts
|

Nutrimetabolomics reveals food-specific compounds in urine of adults consuming a DASH-style diet

Abstract: Although health benefits of the Dietary Approaches to Stop Hypertension (DASH) diet are established, it is not understood which food compounds result in these benefits. We used metabolomics to identify unique compounds from individual foods of a DASH-style diet and determined if these Food-Specific Compounds (FSC) are detectable in urine from participants in a DASH-style dietary study. We also examined relationships between urinary compounds and blood pressure (BP). Nineteen subjects were randomized into 6-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
(18 reference statements)
0
17
0
Order By: Relevance
“…In another recent small study by Reisdorph et al (n = 19), investigators evaluated metabolic profiles of 12 foods common in DASH-style diets. They evaluated urine LC-MS metabolomics and detected many of these food specific metabolites in urine samples from participants consuming the DASH diet, particularly urine phenolic compounds from fruits and vegetables [ 23 ]. This is consistent with our finding of a higher urine phenolic acids in the DASH group which contains higher levels of fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent small study by Reisdorph et al (n = 19), investigators evaluated metabolic profiles of 12 foods common in DASH-style diets. They evaluated urine LC-MS metabolomics and detected many of these food specific metabolites in urine samples from participants consuming the DASH diet, particularly urine phenolic compounds from fruits and vegetables [ 23 ]. This is consistent with our finding of a higher urine phenolic acids in the DASH group which contains higher levels of fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found thiodicarb, 3-Indolebutyric acid and benzenemethanamine derivatives in the Parac-Upper Rimac and Santa Eulalia-Parac localities. The first compound is an agricultural insecticide against some species of Lepidoptera, Coleoptera and Hemiptera [69], the second one is a plant hormone, an ingredient in many commercial horticultural plant rooting products and a food-specific compound that was detected in human urine [70], and the third one is commonly used for the manufacture of plastic. Further sampling efforts should also consider the interaction between microbiota and chemical pollutants, product of anthropogenic activities [16].…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: J Card Fail-Journal of Cardiac Failure; AJCN-American Journal of Clinical Nutrition; Sci Report-Scientific Reports; Hypertension-Journal of Human Hypertension; MNFR-Molecular Nutrition & Food Research; RCT-randomized controlled trial; M-male; F-female; GC-MS-gas chromatography-mass spectrometry; LC-MS-liquid chromatography-mass spectrometry. Two recent small, controlled feeding trials of the DASH pattern demonstrated metabolites specific to the DASH diet and food-specific components reflecting the intervention diet [91,92]. In a HFpEF study using targeted metabolomics, a controlled DASH sodiumrestricted diet resulted in metabolite changes correlated with ventricular contractility and inversely with ventricular stiffness, suggesting metabolically beneficial effects due to dietary modifications [90].…”
Section: Metabolic and Metabolomic Biomarkersmentioning
confidence: 99%